2018
DOI: 10.17161/jas.v4i1.6702
|View full text |Cite
|
Sign up to set email alerts
|

Female Roller Derby Athletes’ Athletic Identity and Systematic Pursuit of Leisure

Abstract: Athletic identity is a foundational element of an individual’s self-concept and affects psychological, social, and behavioral characteristics. The purpose of this study was to investigate a unique sport phenomenon, roller derby, by exploring the relationships between athletic identity of women athletes and serious leisure pursuit in the sport. Participants were 578 women registered with the Women’s Flat Track Derby Association (WFTDA) who completed an online survey concerning their athletic identity. Hierarchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Sport is also often a form of serious leisure (Stebbins.... 1992) that provides participants "small worlds" of social identification, opportunities for learning and developing skills, escape from monotonous and routine work, recognition for commitment and excellence, and a context for the expression of achievement motivations. Within the framework of serious leisure, a wide and diverse range of studies have been conducted over the past three decades with sports being one of the most popular activities in the domain of serious leisure, including master swimmers (Hastings, Kurth, Schloder, & Cyr, 1995) youth sports (Siegenthaler & Gonzalez, 1997) whitewater kayakers (Sherry & Bartram, 2001) dancers (Brown, 2007) cycling (O"Connor & Brown, 2010) playing chess (Gould et al, 2011) taekwondo participation (Kim, Dattilo, & Heo, 2011) amateur athletes (MacCosham, Patry, Beswick, & Gravelle, 2015) competition climbing (Gagnon, Stone, & Garst, 2015) runners (Ronkainen, Harrison, Shuman, & Ryba, 2017) female roller derby athletes (Liu, Baghurst, & Bradley, 2018) and different sets of athletes (Romero, Iraurgi, Madariaga, & Gould, 2020). These studies demonstrated a strong relationship between the serious leisure characteristics of athletes and their leisure involvement and dedication.…”
Section: Introductionmentioning
confidence: 99%
“…Sport is also often a form of serious leisure (Stebbins.... 1992) that provides participants "small worlds" of social identification, opportunities for learning and developing skills, escape from monotonous and routine work, recognition for commitment and excellence, and a context for the expression of achievement motivations. Within the framework of serious leisure, a wide and diverse range of studies have been conducted over the past three decades with sports being one of the most popular activities in the domain of serious leisure, including master swimmers (Hastings, Kurth, Schloder, & Cyr, 1995) youth sports (Siegenthaler & Gonzalez, 1997) whitewater kayakers (Sherry & Bartram, 2001) dancers (Brown, 2007) cycling (O"Connor & Brown, 2010) playing chess (Gould et al, 2011) taekwondo participation (Kim, Dattilo, & Heo, 2011) amateur athletes (MacCosham, Patry, Beswick, & Gravelle, 2015) competition climbing (Gagnon, Stone, & Garst, 2015) runners (Ronkainen, Harrison, Shuman, & Ryba, 2017) female roller derby athletes (Liu, Baghurst, & Bradley, 2018) and different sets of athletes (Romero, Iraurgi, Madariaga, & Gould, 2020). These studies demonstrated a strong relationship between the serious leisure characteristics of athletes and their leisure involvement and dedication.…”
Section: Introductionmentioning
confidence: 99%